Distribution of plasma parameters in the stellarator at neoclassical transport under conditions of recycling - Rudakov, V.A. (Вопросы атомной науки и техники, 2015)
The spatial distributions of plasma parameters in the stellarators LHD and U-2M, operating under recycling conditions with the assumption of neoclassical transport realization, are calculated using the one-dimensional space-time numerical code. The stable solutions of the system of equations for the spatial distributions of ion and electron temperatures, plasma and neutral neutron density and ambipolar electric field are obtained. The flat spots formation in the radial profiles of plasma parameters near the plasma boundary is shown.
PACS: 52.55.HC, 52.25.Fi, 52.25.Ya C использованием одномерного пространственно-временного численного кода рассчитаны пространственные распределения параметров плазмы в стеллараторах LHD и У-2М, работающих в условиях рециклинга в предположении реализации неоклассического переноса. Получены устойчивые решения системы уравнений для пространственных распределений температур ионов и электронов, плотности плазмы и нейтральных атомов, амбиполярного электрического поля. Показано образование плоских участков в радиальных профилях параметров плазмы вблизи границы плазмы. З використанням одновимірного просторово-часового числового коду розраховано просторові розподіли параметрів плазми в стелараторах LHD і У-2М, працюючих в умовах рециклінгу в припущенні реалізації неокласичного перенесення. Отримані стійкі рішення системи рівнянь для просторових розподілів температур іонів і електронів, щільності плазми та нейтральних атомів, амбіполярного електричного поля. Показано утворення плоских ділянок у радіальних профілях параметрів плазми поблизу межі плазми.